FAKTOR KONTAMINASI BAKTERI E. coli PADA MAKANAN JAJANAN DILINGKUNGAN KANTIN SEKOLAH DASAR WILAYAH KECAMATAN BANGKINANG - Yepi Kurniadi; Zulfan Saam; Dedi Afandi (Jurnal Ilmu Lingkungan, 2013)
Today’s food security problem is already a global problem, so that take the main attention insetting public health policy. From the monitor results of Indonesia food and drug regulatorydepartment (POM RI) to outbreak events (KLB) of food poisoning in Indonesia in 2004showed that there had been outbreaks of food poisoning. POM states that the practice ofhygiene and sanitasion are low due to inadequate supply of water, hand washing facilitiesand trash in the neighborhood surrounding the school canteen and school , was the maincause of streetfood safety issues. This study aimed to determine the factor associated with theincidence of contamination of E. coli in streetfood stalls in the primary school environment inthe Kecamatan Bangkinang in 2012 conducted with population 21 primary. This study is across sectional study was conducted in September to Oktober 2012. Subjects in this study isthat three are stalls in the elementary school environment. This study uses primary data isdone by using questionnaire and observation method. The results were obtained picture ofthe food processing are eligible for 17 (81%), presentation of food that did not meetrequirement for 15 (71,4%), construction of building that do not qualify for 14 (66,7%),sanitation facilities are not eligible for 17 (81%) and handlers are not eliglible for 12(57,1%). Bivariant variable results get related variabel presentation of food, facilitiessanitation and handlers. Conclusion that presentation of food, facilities sanitation andhandlers can give bad effect to contamination of Escherichia coli in streetfood stalls.